Os jogos teatrais e a sequência básica de Rildo Cosson na formação do leitor literário no curso de pedagogia - Pinheiro, André de Araújo (2021)
Discussions regarding reading training have increasingly raised the need for new methodological practices in the context of the classroom. In this sense, it is understood that the pedagogue, the professional who weaves the initial knowledge in the school context, in the child's life, must have the appropriation of effective actions and, above all, allow the reader to act in literary reading. The research “Theatrical Games and the Basic Sequence in the Formation of the Literary Reader in the Pedagogy Course” has as general objective to propose an intervention of literary reading formation based on the dialogue between the theatrical games and the basic sequence of Rildo Cosson, The theoretical discussion is initially conceived with Pontes (2012), Candido (1995) and Martins (2006) in the discussion of literary reading, Colomer (2003) and Machado (2016) in the reader training, and also Coelho (2000) and PISA (2012 ; 2015; 2018) in the analysis of reading from the perspective of this research. The second category, which deals with literary literacy and the basic sequence, is overlapped in the studies by Cosson (2007) regarding the basic sequence and Carlino (2017), Azevedo (2004) and Kleiman (2004) with the academic literacy for the potentialities of the literary text. Finally, the third theoretical category brings the perspective of theatrical games, in which we turn to Courtney (2001) to discuss the dramatic text in the classroom and Spolin (2010) and Manzoni (2008) in the game, creativity, spontaneity and theatrical improvisation. The research was constituted, methodologically, in a mixed methods approach, in which quantitative data are analyzed qualitatively, given through an intervention research with a proposal aimed at undergraduate students of the Pedagogy course at the State University of Rio Grande do Norte (UERN). The corpus to be analyzed consisted of an investigative questionnaire, in order to find out how the reading training classes are given, and a basic sequence proposition focusing on the reading of a poem by Manoel de Barros. The results showed the applicability of the stages of the workshops in a proposition thought and experienced in/from the dialogue between theatrical games and the basic sequence. We verified that theatrical games of improvisation, compound stimulus, text fragments and concentric circles converge, respectively, with the steps of the basic sequence, motivation, introduction, reading and interpretation, culminating in a proposal capable of forming readers, with pleasure